Ecotoxicological effects of treated and untreated wastewater on the life cycle of Helix pomatia (Pulmonata) exposed in artificial soil - Semase, Matseleng Pregent (University of the Free State, 2019)
Water treatment plants, which are established to convert wastewater into reusable water of suitable quality are under gross neglect in South Africa. As such, most of these treatment plants do not function optimally. The present study was conducted to determine the ecotoxicological effects of treated and untreated wastewater from the Maluti-A-Phofung wastewater treatment plant in Phuthaditjhaba. To do so, Wastewater samples were collected from the treatment plant, while a total of 300 Individuals of Helix pomatia were purchased from a breeder in Phuthaditjhaba. Each treatment was comprised of 10 snails placed in 2000g of OECD soil spiked with different concentrations (0, 25, 50, 75 and 100%) of wastewater. The ecotoxicological effects of the wastewater were determined by assessing the biomass, survival reproduction (cocoon production and juvenile emergence), and biomarker responses (Catalase activity Acetylcholinesterase) of H. pomatia. The results showed that there was a significant decrease (P<0.05) in the survival of H. pomatia from the control for both treatments groups. Reproduction results showed that there was a significant reduction (P<0.05) in cocoon production between H. pomatia exposed in controls and all the treatments groups for untreated and treated effluent. Similar results were observed for juvenile emergence. The results also indicated that H. pomatia exposed to untreated and treated wastewater showed significant reductions in biomass compared to the control. The differences were between the control groups and 100% groups for both exposure substrates (P < 0.05). An EC10 of 0,425% and EC50 of 6.233% were calculated for juvenile emergence and EC10 of 5,751% and EC50 of 5.751% were calculated for egg production in untreated wastewater. After 60 days of exposure, biomarkers were conducted and the results showed there was no statistical difference in AChE activities for H. pomatia exposed in control soils and soils spiked with treated and untreated wastewater, despite the fact that the activity seemed higher in H. pomatia exposed to soils spiked with treated wastewater. Similar results were found in catalase activity for H. pomatia exposed in soils spiked with treated and untreated wastewater, despite the fact that higher CAT activity seems to occur in the untreated wastewater Results from this study highlight the toxic effects of wastewater pollution in the Maluti A Phofung wastewater treatment plant If the wastewater treatment plant continues to improperly manage their wastewater with similar contents or more continues to improperly manage their wastewater with similar contents or more this this could could lead to lead to a decline in biodiversity, and also contribute to decline in biodiversity, and also contribute to the alteration of alteration of ecosystem balance.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State (Qwaqwa Campus), 2019
Keywords: Acetylcholinesterase; Catalase; Helix pomatia; Reproduction; Survival; Wastewater